An estimate of seasonality and intensity of infection with gastrointestinal nematodes in sheep and goats . in West Java - Beriajaya .; D.B Copeman (Jurnal Ilmu Ternak dan Veteriner, 1998)
Tracer Inoodle tbin-tail sheep and Kacang goats were used to measure the seasonal changes in gastrointestinal nematodes parasitism i ~'und[, .xillapek .Fodd~ 'ofis in West Java . Each 3 months for 12 months worm-free male sheep (5) and goats (5) about 5 months of age were ~ $Jri~tgldI o% ef- farmer, and managed as part of their flock for 2 months . Animals were then returned to the laboratory and maintained on "`~^taaan-ftwAiet in elevated slatted pens for 3 weeks prior to slaughter. In all  trials sheep had higher faecal egg counts than goats . Egg counts were significantly lower during the late dry-early wet season due mainly to lower burdens of Oesophagostomum spp. than at other times of the year. The predominant genera recovered from faecal larval cultures were Haemonchus and Trichostrongylus . At post mortem more than 94 percent of animals were infected with Trichostrongylus colubriformis, T. axei, Haemonchus contortus, Oesophagostomum columbianwn and Strongyloides papillosus . Other species found, in descending order of occurrence, were Cooperia curticei, Trichuris ovis, Bunostornum trigonocephalum, Oesophagostomumn asperum, Capillaria bovis and Gaigena pachycelis. It was concluded that intensity of exposure of both sheep and goats to H contortus, T. axei and C. curticei was similar throughout the year, but that availability of infectioe larvae of T. colubriformis was higher during the dry than the wet season and vise versa for O. columbianum . Sheep had higher burdens of T. Colubrzformis than goats but similar numbers of other species.   Keywords: Thin-tail sheep, kacang goats, tracer, gastrointestinal nematode